2017
DOI: 10.1159/000455006
|View full text |Cite
|
Sign up to set email alerts
|

Direct-to-Consumer Genetic Testing: User Motivations, Decision Making, and Perceived Utility of Results

Abstract: Background/Aims: To describe the interests, decision making, and responses of consumers of direct-to-consumer personal genomic testing (DTC-PGT) services. Methods: Prior to 2013 regulatory restrictions on DTC-PGT services, 1,648 consumers from 2 leading companies completed Web surveys before and after receiving test results. Results: Prior to testing, DTC-PGT consumers were as interested in ancestry (74% very interested) and trait information (72%) as they were in disease risks (72%). Among disease risks, hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
118
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(129 citation statements)
references
References 27 publications
8
118
1
2
Order By: Relevance
“…This is consistent with other research on genetic testing, which generally showed lower interest in genetic testing among people who identified with a religion [20]. In contrast to previous research, we found no association with education [11,31] or gender [8,11,30].…”
Section: Demographic Factorssupporting
confidence: 90%
See 2 more Smart Citations
“…This is consistent with other research on genetic testing, which generally showed lower interest in genetic testing among people who identified with a religion [20]. In contrast to previous research, we found no association with education [11,31] or gender [8,11,30].…”
Section: Demographic Factorssupporting
confidence: 90%
“…These findings may both be explained through different perceived utility. Namely, it was found that actual DTC-GT users with poorer self-reported health [8] and members of the general population with serious disease in the family [20] perceived results as having lower utility. Third, identifying with a religion resulted in lower acceptability of DTC-GT.…”
Section: Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…McClaren et al (2008) showed that potential consumers perceived carrier screening as “not in my world,” and were unlikely to request testing, unless offered by a healthcare professional or if they had a positive family history. Moreover, a study among users of DTC personal genomic testing showed that only one third of the responders was interested in obtaining carrier status information (Roberts et al 2017). The authors argue that this information may not be viewed as personally relevant, or users are unfamiliar with these tests compared to other types of genetic tests (e.g., tests to determine disease risks) (Roberts et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, BGD may be coupled also to large-scale information for environmental exposures and lifestyle (2). People may use BGD for health-related reasons in the context of healthcare delivery or on their own initiative via direct-to-consumer offerings (3). …”
Section: Introductionmentioning
confidence: 99%